Analysis of a Pre-Stressed Quadcopter Propeller Using Finite element Approach - Ahmad, Faraz; Kumar, Pushpendra; Patil, Pravin P. (Journal of Graphic Era University, 2021)
Quadcopter, a mechatronic device is now widely used due to its simple structure and vertical take-off and landing capability. It consists of four propellers which can lift and propelled the Quadcopter in 3-D space. The difference in angular speeds of propellers works as a steering system and responsible for attitude and altitude motion. Quadcopter self weight and pay load is carried by the propellers itself, and a bad design of the propeller may lead to crack. Quadcopter propellers are also subjected to thrust force and vibration during the flight. The main objective of this study is to find out the natural failure frequency of propeller. Two types of propellers have been designed in Creo 2.0 and analyzed in Ansys 16.2 for their vibration frequencies. Both the designs are analyzed with or without the thrust force under the vibration frequency. First six vibration modes have been calculated for both the propeller designs with Carbon Fiber Reinforced Polymer (CFRP) material. The obtained simulation results have been compared and analyzed to sustain the failure frequency.